Design of narrow bandgap non-fullerene acceptors for photovoltaic applications and investigation of non-geminate recombination dynamics. Issue 43 (16th July 2020) - Vollbrecht, Joachim; Lee, Jaewon; Ko, Seo-Jin; Brus, Viktor V.; Karki, Akchheta; Le, William; Seifrid, Martin; Ford, Michael J.; Cho, Kilwon; Bazan, Guillermo C.; Nguyen, Thuc-Quyen
Abstract : A new narrow bandgap non-fullerene electron acceptor was designed, synthesized, and characterized for near-infrared organic photovoltaics. Abstract : A new narrow bandgap non-fullerene electron acceptor was designed, synthesized, and characterized for near-infrared organic photovoltaics. This acceptor was compared to a structurally similar compound with systematically modified side chains, and a series of solar cells were fabricated, employing the common donor polymers PTB7-Th and PBDBT. The devices exhibited charge generation over a wide spectral range and power conversion efficiencies up to 8.1%. The non-geminate recombination dynamics were investigated and quantified via a combination of capacitance spectroscopy and transient open-circuit voltage decay measurements. The reduction of the bandgap results in increased bimolecular recombination losses, while solar cells composed of PBDBT were afflicted by stronger monomolecular, i.e. trap-assisted, recombination losses that ultimately caused the lower power conversion efficiencies of the respective devices. The latter observation could be correlated to less ordered blend film morphology.